Chemical investigation and biological activities of the essential oil of Knema kunstleri Warb. from Malaysia. Issue 13 (15th June 2021) - Salleh, Wan Mohd Nuzul Hakimi Wan; Anuar, Muhammad Zul Afiq; Khamis, Shamsul; Nafiah, Mohd Azlan; Sul'ain, Mohd Dasuki
Abstract: The chemical composition of the essential oil of Knema kunstleri Warb. (Myristicaceae) was investigated for the first time. The essential oil was obtained by hydrodistillation and fully characterized by gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS). In total, 36 components were identified in the essential oil, which made up 91.7% of the total oil. The essential oil is composed mainly of β-caryophyllene (23.2%), bicyclogermacrene (9.6%), δ-cadinene (7.3%), α-humulene (5.7%), and germacrene D (4.3%). The essential oil showed moderate activity towards DPPH free-radical scavenging and lipoxygenase inhibition. To the best of our knowledge, this is the first study of the composition and bioactivities of the essential oil report concerning the genus Knema . Abstract : UF0001